Threats to Economic Security of the Enterprise and Directions of Leveling in Terms of European Integration Processes (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In the article the economic safety system of Ukraine enterprises is ivestigated and attempted to find ways to reduce threats to their activities in terms of European integration.To protect the business from internal threats, exposure and development potential it was offered for the company to create an effective system of personnel management, not simple renaming of staff; development of an individual approach to each employee; development at every job career system, which would depend on the achievements of the man at work, and not on the degree of kinship; increase motivation tangible and intangible ways; creating a system of formation of personnel reserve.Identified possible threats to the economic security of enterprises in the process of interaction with suppliers, customers, competitors and the public administration. Investigated that each interaction can carry an appropriate threat that appears on the results of economic activity of the studied companies and their further development. Considering we identified threats, the ways of providing economic security for businesses on every subject interaction.
Keywords: security, economic security, risks, threats to the economic security of enterprises, European integration